Causal mechanisms that enable institutionalisation of open government data in Kenya - Mungai, Paul (Department of Information Systems, 2018)
Open Government Data (OGD) has become a topic of prominence during the last decade. However, most governments have not realized the desired outcomes from OGD, which implies that the envisaged value streams have not been realized. This study defines three objectives that will help address this shortcoming. First, it seeks to identify the causal mechanisms that lead to effective institutionalization and sustainability of OGD initiatives in a developing country context. Second, it seeks to identify the social, economic, cultural, political structures and components that describe the OGD context. Third, it seeks to identify the underlying contextmechanism- outcome (CMO) configurations in the Kenya Open Data Initiative (KODI). The guiding philosophy for this qualitative study is critical realism, which is implemented using Pawson & Tilley's realist evaluation model. Data is obtained through observation of open data events, semi-structured interviews and documentary materials from websites and policy documents. Fereday & Muir-Cochrane's five-stage thematic analysis model is applied in conducting data analysis. Three main contributions arise from this study. The first contribution is the open data institutionalization analysis guide. This study collates several institutionalization concepts from literature with the aim of developing a lens for analyzing OGD initiatives. The second contribution is the identification of supporting mechanisms, including a description of the current CMO configurations. The resulting case study provides an in-depth account of KODI between 2011 and 2016. This will assist policy makers in understanding the current setup, identifying gaps, and establishing or supporting existing support structures and mechanisms. The third contribution is related to scarcity of empirical work based on critical realism in the field of information systems. This research will act as a reference point for future IS research, in determining how critical realism can be applied to conduct similar studies.